Successful Physician Training Program for Large Scale EMR Implementation - Pantaleoni, J.L.; Stevens, L.A.; Mailes, E.S.; Goad, B.A.; Longhurst, C.A. (Applied Clinical Informatics, 2015)
End-user training is an essential element of electronic medical record (EMR) implementation and frequently suffers from minimal institutional investment. In addition, discussion of successful EMR training programs for physicians is limited in the literature. The authors describe a successful physician-training program at Stanford Children’s Health as part of a large scale EMR implementation. Evaluations of classroom training, obtained at the conclusion of each class, revealed high physician satisfaction with the program. Free-text comments from learners focused on duration and timing of training, the learning environment, quality of the instructors, and specificity of training to their role or department. Based upon participant feedback and institutional experience, best practice recommendations, including physician engagement, curricular design, and assessment of proficiency and recognition, are suggested for future provider EMR training programs. The authors strongly recommend the creation of coursework to group providers by common workflow.Citation: Pantaleoni JL, Stevens LA, Mailes ES, Goad BA, Longhurst CA. Successful physician training program for large scale EMR implementation. Appl Clin Inf 2015; 6: 80–95http://dx.doi.org/10.4338/ACI-2014-09-CR-0076
Keywords: Physician; education; electronic medical records